PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KEJELASAN SASARAN ANGGARAN, KOMITMEN APARATUR TERHADAP KINERJA MANAJERIAL DENGAN JOB RELEVANT INFORMATION (JRI) SEBAGAI VARIABEL INTERVENING - Ridzal, Nining Asniar; wawo, andi basru; husin, husin (Pascasarjana Universitas Halu Oleo, 2016)
The aim of this study was to analyze the impact of participation in budgeting, clarity of budgeting targets, and staff commitment on managerial performance, with job relevant information working as an intervening variable. The study was a causal research, involving 28 SKPD of Baubau City government as the objects of the study. Samples of the study were Head of Agency. Head of Office, Head of Sub-Section of Finance, Head of Sub-Section of Planning/Program, and Heads of Section in each SKPD. Data were collected using a questionnaire. The data were then analyzed using the path analysys on the SPSS version 20.Result of partial analysis showed that participation in budgeting had a positively insignificant effect on job relevant information, clarity of budgeting targets had a positively significant effect on job relevant information, staff commitment had a positively significant effect on job relevant information. furthermore, participation in budgeting had a positively significant effect on managerial performance, clarity of budgeting targets had a positively significant effect on managerial performance, staff commitment had a positively significant effect on managerial performance, and job relevant information had a positively significant effect on managerial performance. Results of simultaneous analysis showed that participation in budgeting, clarity of budgeting targets, and staff commitment had an effect on job relevant information. participation in budgeting, clarity of budgeting targets, and staff commitment had an effect on managerial performance. Job relevant information is not capable of acting as an intervening variable between participation in budgeting on managerial performance, job relevant information is not capable of acting as an intervening variable between clarity of budgeting targets on managerial performance, and job relevant information is not capable of acting as an intervening variable between the staff commitment on managerial performance.Â Keywords: Participation in budgeting, clarity of budgeting targets, staff commitment, job relevant information, managerial performance.